Effects of minor rhenium additions on the thermal properties and recrystallization temperature of tungsten alloy - Jinbo Shi; Jiupeng Song; Mengxia Liang; Youyun Lian; Jianbao Wang; Fan Feng; Xiang Liu (Nuclear Materials and Energy, 2024)
Tungsten (W) stands out as a highly promising plasma-facing materials (PFMs) for future nuclear fusion reactors due to its advantages of excellent high temperature strength, low tritium retention and high recrystallization temperature (RCT). Notably, the potassium-doped tungsten-rhenium (W-Re-K) alloy exhibits exceptional performance when compared to other potential W-based alloys. Nevertheless, even a small amount of Re addition can reduce the thermal conductivity of W, which falls short of the requirement for PFMs. In this study, W-Re-K alloys with Re addition from 0.1 wt% to 0.5 wt% and minor K doping (40 ∼ 50 ppm) were manufactured via powder metallurgy and thermo-mechanical processes. The results revealed that the presence of Re had a grain-refining effect, which became more obvious as its content increased. The incorporation of a small amount of Re (W-0.5 wt% Re-K) exhibited favorable characteristics. Featuring an average grain size of 20.25 µm, and displayed a room temperature thermal conductivity of 163 W/(m⋅K), and an elevated RCT of approximately 1588 °C.